A dog's purpose - Cameron, W. Bruce (New York : Forge, 2010)
Searching for his purpose over the course of multiple canine lives, Bailey is reborn as a golden-haired puppy after a tragic death as a stray and shares a loving bond with young Ethan before he again dies and starts over.
"A Tom Doherty Associates book."
Keywords: Dogs -- Fiction; Human-animal relationships -- Fiction; Reincarnation -- Fiction